Directions of recovery of enterprises financial stability - Maryna Kravchenko (Cхід, 2013)
There has been defined the essence of main directions of financial stability recovery, which presuppose modernization of an enterprise, improvement of costs management, price policy and product distribution policy, improvement of enterprises finance management.